Ethyl Carbamate Production Kinetics during Wine Storage - Xue, J.; Fu, F.; Liang, M.; Zhao, C.; Wang, D.; Wu, Y. (South African Journal of Enology and Viticulture, 2016)
The kinetics of ethyl carbamate (EC) formation was investigated during wine storage to evaluate the potential risk of EC formation in wine. The study monitored the EC, urea and citrulline concentration at different storage temperatures and wine pH. We found that temperature and initial urea content had significant effects on EC formation. The decay of urea and citrulline fit a first-order reaction approaching equilibrium, but the pH has little effect on the content of ethyl carbamate. Based on these results, we constructed an equation to forecast the content of ethyl carbamate during wine storage.